Sosialisasi Literasi Keuangan Syariah di Desa Cacaban, Kecamatan Conggeang, Kabupaten Sumedang - Dinda Emmy Gusti Sofhia; Juli Wicaksono; Deni Lubis (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
This community service activity aims to educate the public about BMT (Baitul Mal wal Tamwil) and Sharia cooperatives and provide an understanding to the village community regarding sharia finance. The main target from the socialization activities of Islamic financial literacy are BUMDes members, cooperative management, village office staff, and youth organizations in Cacaban Village, Conggeang District, Sumedang Regency. The implementation of the activity was carried out in the form of sharing sessions by the implementing team of community service to IPB which was carried out in two stages namely, presentation and discussion. Based on the results of the activities that have been carried out that the participants were very enthusiastic about listening to the socialization material and playing an active role during the question and answer process about the importance of community literacy in the world of Islamic financial institutions to improve their welfare and improve economic growth in Cacaban Village. After this sharia financial literacy socialization activity, the community of Cababan Village gained new knowledge about BMT (Baitul Mal wal Tamwil) and sharia cooperatives, as well as about sharia finance which could become an alternative in financial management in village financial institutions. Key words: BMT, islamic cooperatives, islamic financial literacy